A inaplicabilidade do direito ao esquecimento na era digital - Seben, Valentinna Oltramari (My University, 2024)
The general objective of this work was to analyze the inapplicability of the right to be forgotten as a legal protection in the digital age. The research aimed to understand the evolution of the digital society, the emergence and development of the right to be forgotten. Developed in three chapters, the study has a theoretical nature and was based on analyses of doctrine, Brazilian legislation and jurisprudence. The first chapter addresses the emergence of the General Data Protection Law and its objectives, how the control of personal data occurs in modernity and the application of the principle of human dignity in the digital age, providing an introductory view of what would be treated as the main theme. In the second chapter, the insertion of fundamental rights and guarantees in contemporaneity was explored, its historical evolution and the changes that occurred so that there would be an adaptation to the digital society. In the third chapter, the right to be forgotten was specifically addressed, in order to explain its emergence both in the Brazilian legal system and in other countries, and its inapplicability as a legal protection in modern times. It was concluded that the Superior Courts, when it is necessary to use the weighting method due to the collision between the right to be forgotten and some other fundamental right, do not apply the right to be forgotten as a legal remedy, due to the speed and ease with which information spreads. [resumo fornecido pelo autor]
O presente trabalho teve como objetivo geral analisar a inaplicabilidade do direito ao esquecimento como tutela jurídica na era digital. A pesquisa visou à compreensão da evolução da sociedade digital, o surgimento e desenvolvimento do direito ao esquecimento. Desenvolvido em três capítulos, o estudo possui natureza teórica e baseou-se em análises da doutrina, legislação brasileira e jurisprudências. O primeiro capítulo abordou o surgimento da Lei Geral de Proteção de Dados e seus objetivos, como ocorre o controle de dados pessoais na modernidade e a aplicação do princípio da dignidade da pessoa humana na era digital, proporcionando uma visão introdutória do que seria tratado como tema principal. No segundo capítulo foi explorado a inserção dos direitos e garantias fundamentais na contemporaneidade, sua evolução histórica e as mudanças ocorridas para que houvesse uma adequação com a sociedade digital. No terceiro capítulo, o direito ao esquecimento foi especificamente abordado, de forma a explicar seu surgimento tanto no ordenamento jurídico brasileiro, quanto em outros países, e sua inaplicabilidade como tutela jurídica nos tempos modernos. Concluiu-se que os Tribunais Superiores, quando necessário a utilização do método da ponderação devido à colisão entre o direito ao esquecimento e algum outro direito fundamental, não aplicam o direito ao esquecimento como tutela jurídica e, mesmo que houvesse a aplicação, não seria eficaz, devido à velocidade e facilidade com que as informações propagam-se. [resumo fornecido pelo autor]
Keywords: Direito ao esquecimento; Proteção de dados; Direitos e garantias individuais; Internet - Aspectos jurídicos